(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
In this paper a new methodology for the morphometric analysis of the Ammonite shell is proposed. It is based on the measurements of ventral and umbilical radii, of section width and rib number. A practical application for the analysis of pliensbachian species of Ammonites collected in some Catria sections is also presented.